“A morte da higiene pública” : os impactos socioeconômicos do surto epidêmico de sarampo em Patrocínio do Coité (BA) entre os anos de 1920 e 1930 - Santos, Marcos Paixão Bastos dos (2022)
The present work sought to understand, through Social History, the transformations of the daily life of the society of Patrocínio do Coité (BA), motivated by the creation of hygienist policies that emerged after the measles epidemic in the 1920s. The dissertation used primary and secondary sources to identify the economic and social relations of an epidemic with the bad habits of the local population. At the same time, it made it possible to understand the factors for the emergence of miasmatic and contagious diseases. Regarding the methodology, were qualitatively examined the data collected in the newspaper O Paladino (1919-1939) and in other sources, such as the Posture Code (1927), Bahia State Reports (1924-1926), and Photographs. The analysis focused on the ills of the population that, together with the climatic conditions, triggered epidemic outbreaks that resulted in fatal victims among the child and adult population; it also stops at the study of the position of the authorities in the face of the dilemmas of hygienist policies.